Implementation of Competency Based Dynamic Curriculum (CBDC) & Entrustable Professional Activities (EPA) – A Perspective. (Homoeopathy for All, 2025)
A fundamental change in how  homoeopathy must be learnt and  experienced by students and teachers  is the core of the Competency Based  Dynamic Curriculum (CBDC) for  BHMS and Entrustable Professional  Activities (EPA) for MD (Hom)  based curriculum. The logic behind it is very  simple, we treat a patient, and a  patient represents disruption of his  anatomy, physiology, biochemistry,  pathology, medicine, surgery when  he meets a homoeopath for seeking  clinical help.  When the patient meets a  homoeopath, homoeopath in  addition to the above-mentioned  knowledge looks back on his  tools (Repertory), therapeutic  armamentarium at disposal (Materia  Medica) and the philosophical stand  which he must use to approach the  patient to justify the application of  the first six aphorisms (Organon). When he sits in his clinic he  sits with all this knowledge, skill  and attitude he is supposed to have  acquired. However, in his post  college days, he decides to undergo  personal training under someone  whom he believes will help establish  as a homeopath or learn the hard way  by sitting in the clinic or setting up  a hospital in which he treats patients  becomes competent over a period of  time.
Keywords: horizontal integration; outreach initiatives; futuristic methodology; dynamic